Inteligência tributária urbano-ambiental: extrafiscalidade dos tributos municipais como instrumento de concretização da cidade sustentável - Mota, Hector Ruslan Rodrigues (2021)
The research is based on the centrality of the urban environment for contemporary debates on the fundamental right to a balanced environment for present and future generations, as well as the instrumentalization of tax law in municipal and extrafiscal scope, as a tool for the realization of the right to the sustainable city in Brazil. The research problem is to assess whether the current system of municipal taxes proposed by the Brazilian Federal Constitution is sufficient to implement, through extrafiscal tools, the right to having sustainable cities. The research uses a hypothetical-deductive approach and bibliographic and documentary research techniques, focusing on Brazilian and international doctrine and legislation. It started from the hypothesis that the current model can be, based on the guidelines indicated by the Constitution and legislation, adapted to the reality of inducing behaviors towards environmental urban planning. After reaching the specific objectives that are faced in each chapter of this dissertation, it was possible to confirm the research hypothesis with the addition of additional conclusions about the interaction between municipal environmental taxation and other urban policies with a view to sustainable urban development. It is a study with a legal-projective characteristic, aiming at the detection of possible ways for the adaptation of environmental taxation to the contemporary reality that calls for the need for urban environments that provide a dignified life to the inhabitants, since it is proposed to build a model of environmental taxation that reflects and materializes the urgent need to transform Brazilian cities into spaces of sustainability and dignified life, following guidelines of constitutional principle matrix.